RANCANG BANGUN SISTEM PENGELOLAAN DATA DAN PENYEDIAAN SUKU CADANG SEBAGAI PENUNJANG PRODUKSI - Rudy Yandri; Rosmawati Dwi; Kurnia Damayanti (UNIVERSITAS RAHARJA, 2019)
The process of managing spare parts supply data at this time in some companies is still ineffective, because the process is still manually using ledgers to archive data that has been managed, this requires a long time so it is not efficient. To overcome the above problems, a computerized system is needed so that it can overcome problems and speed up the process. Therefore, this study proposes the design of a system of providing spare parts automatically based on various methods of data collection, analysis using PIECES to evaluate system performance and design which includes UML (Unified Modeling Language) as a tool to help object-oriented programming languages and use MySQL as a database , which in the end will produce a system that is well integrated. So from this research it is useful to facilitate the process of achieving company targets and to streamline the quality control system on production machines.